Outpatient approaches to the treatment of novel coronavirus infection in pregnant and lactating women - A. V. Mordyk; L. V. Puzyreva; K. Yu. Samsonov; N. V. Bagisheva (Лечащий Врач)
The problem of treating the new coronavirus infection COVID-19 in pregnant and lactating women is an urgent problem of world health. According to foreign authors (Mantlo E., Bukreyeva N., Maruyama J., Paessler S., Huang C. Antiviral activities of type I interferons to SARS-CoV-2 infection. Antiviral Res. 2020 Jul; 179: 104811) recombinant interferon α is active against the novel coronavirus in vitro in the cell culture model Vero and SARS-CoV-2 (COVID-19). SARS-CoV-2 (COVID-19) is sensitive to recombinant interferon α-2b, but high serum concentrations (more than 300 IU / ml) are required to achieve a therapeutic effect, which are achieved with systemic administration of more than 3,000,000 IU of recombinant interferon α -2b. The article analyzes the clinical symptoms and the effectiveness of therapy for the new coronavirus infection COVID-19 in pregnant and lactating women in outpatient practice with high doses of interferon α-2b (by the decision of the council of doctors). The authors found that complex therapy with high doses of interferon α-2b infection COVID-19 in pregnant women flows relatively favorably and ends with recovery. In lactating women who do not work because of parental leave, the new coronavirus infection had mild clinical symptoms and was accompanied by the development of pneumonia (MSCT I – II) with uncommon lung involvement. As a basic therapy, as well as pregnant women, they were prescribed high doses of recombinant interferon α-2b and β-lactam antibiotic to prevent aggravation of the condition. This therapy made it possible to avoid complications and stop the symptoms of damage to the bronchial tree.